Construction and Activity Testing of a Modular Fusion Peptide against Enterococcus faecalis - Salim Manoharadas; Mohammad Altaf; Naushad Ahmad; Abdulwahed Fahad Alrefaei; Basel F. Al-Rayes (Antibiotics, 2023)
The emergence of antibiotic resistance in enterococci is a great concern encountered worldwide. Almost all enterococci exhibit significant levels of resistance to penicillin, ampicillin, semi-synthetic penicillin and most cephalosporins, primarily due to the expression of low-affinity penicillin-binding proteins. The development of new and novel antibacterial agents against enterococci is a significant need of the hour. In this research, we have constructed a modular peptide against Enterococcus faecalis. The enzymatic domain of the constructed peptide BP404 is from the bacteriocin BacL1 and the cell wall binding domain from endolysin PlyV12 of phage ϕ1. The protein BP404 was found to be active against two tested strains of Enterococcus faecalis, with a reduction in cell density amounting to 85% and 65%. The cell wall binding assay confirms the binding of the protein to Enterococcus faecalis, which was not seen towards the control strain Escherichia coli, invariably pointing to the specificity of BP404. To the best of our knowledge, this is one of the first instances of the development of a chimeric peptide against Enterococcus faecalis. This study points out that novel proteins can be genetically engineered against clinically relevant enterococci.